The making of cultural policy : a European perspective - Frederick van der Ploeg (Center for Economic Studies and ifo Institute (CESifo), 2005)
No good comparable data on sizes of cultural sectors of the countries of Europe exist. Still, local and national governments of Europe spend substantial resources on culture and cultural sectors contribute significantly to employment and national income. After briefly describing special features of cultural goods and clarifying some misconceptions about the value of culture, valid and invalid arguments for subsidising culture are discussed. Although it is easy to justify government support for preservation of heritage, this is more difficult for the performing arts. Due to changing technologies and advent of E-culture classic public-good arguments for government intervention in broadcasting and other cultural activities become less relevant. Different institutions varying from selection by arts councils, bureaucrats or politicians to less directed tax incentives lead to different cultural landscapes. Theories of delegation suggest delegating the judgement on artistic qualities and execution of cultural policy to an independent Arts Fund. The Minister of Culture should concentrate on formulating a mission for cultural policy and make sure it is implemented properly. The insights of the theories of local public goods and federalism are applied to the making of cultural policy in Europe. Different approaches to international cultural policy in Europe are discussed. The overview concludes with lessons for the making of cultural policy in Europe.
Keywords: Z11; H2; P51; H4; 330; cultural policy; heritage; performing arts; museums; quality; participation; vouchers; tax incentives; quality; politicians; bureaucrats; Kulturpolitik; Öffentliches Gut; Organisation; Kulturökonomik; Public Choice; EU-Staaten